The human microbiome-derived antimicrobial lugdunin self-regulates its biosynthesis by a feed-forward mechanism - Leonie Reetz; Lukas Schulze; Thales Kronenberger; Khaled A. Selim; Timm Schaefle; Taulant Dema; Alexander Zipperer; Jens Mößner; Antti Poso; Stephanie Grond; Andreas Peschel; Bernhard Krismer (mBio)
ABSTRACT Many human microbiome members inhibit bacterial competitors by production of antimicrobial compounds whose expression needs to be tightly controlled to balance the costs and benefits of compound biosynthesis. The nasal commensal Staphylococcus lugdunensis outcompetes Staphylococcus aureus using the antimicrobial lugdunin. The lugdunin biosynthetic gene cluster (BGC) encodes two potential regulators whose roles have remained unknown. Deletion of the regulator genes lugR or lugJ led to increased lugdunin production and/or immunity. While LugR was found to repress the transcription of the biosynthetic lugRABCTDZ operon, LugJ repressed the lugIEFGH export and immunity genes. Both regulators bound to different inverted repeats in the controlled promoter regions. Notably, both repressors were released from cognate promoters to allow transcription upon addition of exogenous lugdunin. Even minor structural changes disabled lugdunin derivatives to induce expression of its BGC, which is consistent with inferior binding to the predicted LugR and LugJ binding pockets. Thus, lugdunin controls its own biosynthesis through a feed-forward mechanism probably to avoid futile production.IMPORTANCEBiosynthetic gene clusters (BGCs) are usually tightly controlled to avoid production of costly goods at inappropriate time points or unfavorable conditions. However, in most cases, the regulatory signals of these clusters have remained unknown. Frequently, quorum sensing or two-component regulatory systems are involved in BGC expression control. This study elucidates the sophisticated regulation of lugdunin biosynthesis and secretion via two independent regulators, LugR and LugJ. Although belonging to different families of repressors, both directly interact with the antimicrobial lugdunin and thereby enhance biosynthesis and secretion in a feed forward-like mechanism.